Analisis Tingkat Kesehatan Bank Umum Syariah Yang Terdaftar di BEI Dengan Menggunakan Metode RGEC - Jalaluddin; Hayatul Millah; Ahmad Fajri (DPPM Universitas Pelita Bangsa, 2025)
This study aims to analyze the financial health of Islamic commercial banks listed on the Indonesia Stock Exchange (IDX) using the RGEC method (Risk Profile, Good Corporate Governance, Earnings, and Capital) during the 2021–2024 period. This is a descriptive quantitative study with a documentation approach based on annual reports. The sample consists of four banks selected purposively. The results show that, in general, the four banks are in a healthy condition. Financing risk (Non-Performing Financing/NPF) and liquidity risk (Financing to Deposit Ratio/FDR) fall into the good category. GCG assessment indicates a reasonably sound level. In terms of Earnings, Return on Assets (ROA) and Operating Efficiency Ratio (BOPO) reflect relatively good financial performance despite annual fluctuations. Meanwhile, the Capital Adequacy Ratio (CAR) shows a very strong Capital position. These findings conclude that Islamic commercial banks listed on the IDX have maintained their financial health throughout the observation period, although improvements in operational efficiency and corporate governance are still needed.